THE FEMINIST PERSPECTIVE IN NAYANTARA SAHGAL’S RICH LIKE US AND MARGARET ATWOOD’S SURFACING (International Journal of Food and Nutritional Sciences, 2020)
The countries, which were once used to be under the British hegemony and emerged independent with the withdrawal of the British subsequently, are termed as the Commonwealth countries. These countries though differ from one another in terms of history, traditions, culture, socio-economic conditions, political and geographical identities, share a common experience of being subject nations to the serfdom of the British yoke and the collective literary inheritance of the English. Ergo, the literature contributed henceforth in English in these countries has come to be designated as commonwealth literature. This paper attempts to analyze the feminist viewpoint in the novels of Nayantara Sahgal and Margaret Atwood. Sahgal is one of the renowned contemporary women novelists in Indian Writing in English. Whereas, Atwood is one of the legendary acclaimed women writers in Canada. Liberation of women from domineering oppression of the patriarchal society in the postmodern times receives the focal point in the writings of both Sahgal and Atwood. Both of them attempt to dovetail the submissive and suppressed predicament of women in all walks of life. They seek to attack the gender-based discrimination and treatment meted out to women in social and political domains. They make an effort to look into the deep-rooted subconscious levels, the struggles and conflicts of women in a vivid manner. For the present analysis, Nayantara Sahgal’s Rich Like Us, and Margaret Atwood’s Surfacing are considered. Sonali in Rich Like Us and an unnamed female lead character in Surfacing stand as manifestation of feminist perspective of the respective authors. Both of them put up with multiple tribulations and emerge self-actualizing in the end.